2013
DOI: 10.1542/peds.2012-3494
|View full text |Cite|
|
Sign up to set email alerts
|

Management of Newly Diagnosed Type 2 Diabetes Mellitus (T2DM) in Children and Adolescents

Abstract: Over the past 3 decades, the prevalence of childhood obesity has increased dramatically in North America, ushering in a variety of health problems, including type 2 diabetes mellitus (T2DM), which previously was not typically seen until much later in life. The rapid emergence of childhood T2DM poses challenges to many physicians who find themselves generally ill-equipped to treat adult diseases encountered in children. This clinical practice guideline was developed to provide evidence-based recommendations on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
238
0
13

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 279 publications
(265 citation statements)
references
References 69 publications
4
238
0
13
Order By: Relevance
“…The TODAY study, a large US multicentre randomised clinical trial comparing treatment options for 699 10-to 17-year-olds with type 2 diabetes, found that therapy based on current clinical practice guidelines [6] (metformin plus lifestyle intervention) was ineffective for maintaining glycaemic control in nearly 50% of participants after 1 year of treatment, despite 6 months of weekly face-to-face sessions [36]; hence, the TODAY study, together with the evidence for early diabetes-related complications [3,4], highlights the need for aggressive therapies that commence immediately or early after diagnosis. Bariatric surgery may be a feasible alternative, with one study demonstrating reversal of type 2 diabetes in ten of 11 adolescents [37].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The TODAY study, a large US multicentre randomised clinical trial comparing treatment options for 699 10-to 17-year-olds with type 2 diabetes, found that therapy based on current clinical practice guidelines [6] (metformin plus lifestyle intervention) was ineffective for maintaining glycaemic control in nearly 50% of participants after 1 year of treatment, despite 6 months of weekly face-to-face sessions [36]; hence, the TODAY study, together with the evidence for early diabetes-related complications [3,4], highlights the need for aggressive therapies that commence immediately or early after diagnosis. Bariatric surgery may be a feasible alternative, with one study demonstrating reversal of type 2 diabetes in ten of 11 adolescents [37].…”
Section: Discussionmentioning
confidence: 99%
“…However, regular physical activity was encouraged, consistent with guidelines for type 2 diabetes management in youth [6]. Participants were given an interactive pedometer (Fitbit One; Fitbit, San Francisco, CA, USA) to encourage activity, allowing monitoring and appropriate support from the study dietitian.…”
Section: Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bariatric surgery has proved its usefulness in adults and now it is being applied to children and adolescents with notable improvements of comorbidities, although an experienced setting is required. Concerning the use of metformin in T2D, the initial enthusiasm has waned and probably the concomitant use of insulin would be advisable [70]. The long-acting basal insulin analogs such as insulin detemir, insulin glargine or even insulin degludec [71] used in the adult reduce nocturnal hypoglycemic episodes and can be used in pediatric patients in not well controlled type 2 diabetic patients.…”
Section: Preventive and Therapeutic Aspectsmentioning
confidence: 99%
“…Al ser la obesidad y sobrepeso, los factores de riesgo modificables más importantes para la aparición de DM2 en niños, es importante desarrollar programas educativos que incidan en el control del peso corporal y la adopción de estilos de vida saludables (10) . Experiencias anteriores en otros países han tenido efectos contradictorios, probablemente debido al uso incorrecto de los componentes encargados de la modificación sostenible de conductas de riesgo (11,12) .…”
Section: Introductionunclassified